Sistem Informasi Akomodasi Pariwisata Nusa Dua Berbasis Android - Rifky Lana Rahardian; I Kadek Yogi Wiguna; Revata Siri Ananda (Journal of Innovation Information Technology and Application (JINITA), 2021)
There are lots of Nusa Dua tourism accommodation and it is interesting to be visited by domestic and foreign tourists. The author considers the need for a special portal to provide information about geography Nusa Dua tourism accommodation, in addition to this, it can also increase the interest of foreign tourists to travel with complete information without worrying. An android-based Nusa Dua tourism accommodation information system was created to provide broad information about the availability of the accommodation places in Nusa Dua. This geography information system was built using the waterfall method starting with the needs analysis, system design, coding, and testing stages. The information system built can run and function well in accordance with the needs of tourists, where the system can support tourism activities. The system is able to provide information in the form of writing, pictures and payments to increase the interest of foreign tourists visiting, especially in Nusa Dua.